LANGKAT DISTRICT MUSEUM DESIGN USING A MALAY NEO VERNACULAR APPROACH - Suwantoro, Hajar; Pratama, Rizky Aryan (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Langkat Regency, as one of the districts in North Sumatra, has a long and rich history with strong cultural and religious influences, especially in the Malay Sultanate. Therefore, it is important to preserve these historical relics and the need for a suitable place to store these historical relics. In Tanjung Pura District there is a historical museum building in Langkat Regency, but this building is now less active and less suitable to be used as a museum which should be like a museum. -Other active museums. By redesigning the Langkat Regency museum building, applying the Neo Vernacular Malay approach, where the Langkat area is a Malay land, it can be hoped that its function will be active again so that the local community and the outside community can see it again and become a means of education about the history and heritage of the Langkat Regency area..